DEVELOPMENT OF A TEACHING AT THE RIGHT LEVEL (TARL)-BASED E-LKPD ON SOCIAL ARITHMETIC TO IMPROVE STUDENTS’ CRITICAL REASONING SKILLS - Sinta Nuraeni; Nani Ratnaningsih; Puji Lestari (EMTEKA: Jurnal Pendidikan Matematika, 2026)
This study aims to develop an E-LKPD based on Teaching at the Right Level (TaRL) and to analyze the improvement of students’ critical reasoning skills. The study was conducted with 29 seventh-grade students of class VII B at MTs Ar-Rahmah, Tasikmalaya City, using a Research and Development (R&D) method with the ADDIE model, which includes the stages of analyze, design, development, implementation, and evaluation. Data were collected through observation, interviews, critical reasoning tests, and questionnaires, with instruments consisting of expert validation sheets, response questionnaires, and test items. The results showed that in the analyze stage, learning was still procedural and had not implemented differentiation. The design stage produced a differentiated E-LKPD consisting of three ability levels: need guidance, proficient, and advanced. In the development stage, the product was categorized as highly feasible, with material validity of 88%, media validity of 93%, and test instrument validity of 85%. The product was also considered highly practical based on teacher responses (84%) and student responses (80.86%). During the implementation stage, learning was conducted in three meetings. In the evaluation stage, there was a significant improvement in students’ critical reasoning skills, indicated by an increase in the mean score from 21.72 to 76.59, an N-Gain score of 0.70 (high category), and the paired sample t-test result showing p = 0.000 (<0.05). Therefore, the TaRL-based E-LKPD is effective in improving students’ critical reasoning skills. Penelitian ini bertujuan untuk mengembangkan E-LKPD berbasis Teaching at the Right Level (TaRL) serta menganalisis peningkatan kemampuan bernalar kritis peserta didik. Penelitian dilaksanakan pada 29 peserta didik kelas VII B MTs Ar-Rahmah Kota Tasikmalaya dengan menggunakan metode Research and Development (R&D) model ADDIE yang meliputi tahap analyze, design, development, implementation, dan evaluation. Teknik pengumpulan data meliputi observasi, wawancara, tes kemampuan bernalar kritis, dan angket, dengan instrumen berupa lembar validasi ahli, angket respon, dan soal tes. Hasil penelitian menunjukkan bahwa pada tahap analyze, pembelajaran masih bersifat prosedural dan belum menerapkan diferensiasi. Tahap design menghasilkan E-LKPD terdiferensiasi dalam tiga level kemampuan, yaitu perlu bimbingan, cakap, dan mahir. Pada tahap development, produk dinyatakan sangat layak dengan persentase kelayakan materi 88%, media 93%, dan instrumen tes 85%. Produk juga tergolong sangat praktis berdasarkan respon guru sebesar 84% dan peserta didik sebesar 80,86%. Pada tahap implementation, pembelajaran dilaksanakan dalam tiga pertemuan. Tahap evaluation menunjukkan adanya peningkatan signifikan kemampuan bernalar kritis, ditandai dengan peningkatan rata-rata nilai dari 21,72 menjadi 76,59, nilai N-Gain sebesar 0,70 (kategori tinggi), serta hasil uji paired sample t-test menunjukkan p = 0,000 (<0,05). Dengan demikian, E-LKPD berbasis TaRL efektif dalam meningkatkan kemampuan bernalar kritis peserta didik.